MANAJEMEN RUMAH JURNAL SEBAGAI STRATEGI PENINGKATAN AKREDITASI DAN KEAKTIFAN PUBLIKASI ILMIAH DI STIT AL IHSAN BALEENDAH - Ningarumsari, Rike Junia; Wasliman, Eva Dianawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study analyzes the management of the Al-Idrak Journal as part of the Journal House strategy at STIT Al-Ihsan Baleendah to improve accreditation and enhance scientific publication activity. The main issue addressed in this research is the incomplete fulfillment of several national accreditation indicators, particularly those related to article history transparency, metadata completeness, digital identification, indexing quality, and the diversity of authors and reviewers. This study aims to map the current condition of journal management, identify its strengths and weaknesses, and formulate strategies for improving journal quality. Using a qualitative approach with a content analysis method, this research systematically examines OJS pages, editorial policies, publication consistency, reviewer profiles, indexing status, metadata completeness, and other digital documents. The findings show that although Al-Idrak has met several basic elements of journal management, such as ISSN registration, OJS implementation, and an editorial structure, several strategic components remain unfulfilled, including editorial process transparency, DOI implementation, Creative Commons licensing, standardized metadata, national indexing, and author diversification. These conditions indicate that the journal is still at a foundational management stage and requires substantial improvements to meet national accreditation standards. This study recommends strengthening digital documentation, enhancing editorial professionalism, expanding author networks, diversifying reviewers, and optimizing the role of the Journal House as a center for institutional publication development. Keywords: journal management, Open Journal System (OJS), accreditation